2013
DOI: 10.1097/01.mib.0000436274.95722.e5
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal Perineal Ultrasound Versus Magnetic Resonance Imaging In the Assessment of Perianal Crohnʼs Disease

Abstract: TPUS is a simple and accurate diagnostic method for classifying perianal fistulae in CD and could be used for the preliminary assessment and follow-up of perianal CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 28 publications
2
49
0
Order By: Relevance
“…Images should be documented using the corresponding system for ERUS. PNUS is more flexible than ERUS, particularly when oblique orientated trans-sphincteric fistulas are to be examined [117,118,[120][121][122][123]. Considering that perianal fistulas and/or abscesses have been found in about 10% of newly diagnosed CD pediatric patients, an immediately available and noninvasive diagnostic tool such as PNUS would be of great benefit for further management and follow-up of affected children (FIGURE 6) [124].…”
Section: Other Sonographic Techniquesmentioning
confidence: 99%
“…Images should be documented using the corresponding system for ERUS. PNUS is more flexible than ERUS, particularly when oblique orientated trans-sphincteric fistulas are to be examined [117,118,[120][121][122][123]. Considering that perianal fistulas and/or abscesses have been found in about 10% of newly diagnosed CD pediatric patients, an immediately available and noninvasive diagnostic tool such as PNUS would be of great benefit for further management and follow-up of affected children (FIGURE 6) [124].…”
Section: Other Sonographic Techniquesmentioning
confidence: 99%
“…Studies published by Wedemeyer et al [27] and Maconi et al [28,31] showed that TPUS has a high sensitivity and specificity in detecting perianal disease comparable to those of MRI and EAUS. A study by Rasul et al [32] showed that TPUS can be used to follow perianal fistulas in Crohn's disease patients, concerning therapeutic response.…”
Section: Major Applications In Gastroenterologymentioning
confidence: 92%
“…Its availability and cost-effectiveness enable perianal ultrasound to monitor real-time recovery of fistulas, thus more expensive MRI might be avoided. Maconi et al[45] showed that the sensitivity of TPUS is relatively poor in the identification of extrasphincteric and suprasphincteric fistulas (55.6% and 50%), but it demonstrated an excellent sensitivity and PPV in the recognition of anovaginal and transsphincteric fistulas (sensitivity: 100% and 90%; PPV: 99.4% and 100%). No special preparation and instrumentation is required, and it can be easily mastered, thus perianal ultrasound might be well applied in gastroenterology and proctology; it can be a fast diagnostic tool as well, especially in urgent cases[17].…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%